Organizational Communication Climate of Human Rights Promotion Support Bureau During Covid-19 Pandemi - Delsy Nike; Amri Dunan (LPPM Stikosa - AWS, 2023)
Public Health Emergency of International Concern (PHEIC) over the Coronavirus Disease of 2019 (COVID-19) outbreak by the World Health Organization (WHO) as a global pandemic has threatened public health. This not only triggers changes in health and social and economic norms, but also has an impact on changes in organizational communication norms and processes, interactions between people and the use of new media which causes the organizational communication climate to adapt to situations and conditions that occur. The Bureau of Support for the Promotion of Human Rights on Indonesian National Human Rights Commission is one of the state organizations or institutions that has the duty and authority to promote human rights. This study aims to explore the organizational communication climate and media innovation applied at the Human Rights Promotion Support Bureau of the Indonesian National Human Rights Commission and to find out more about the organization's strategic policies and their implications during the COVID-19 pandemic related to achieving organizational goals. This study uses a qualitative research approach with a constructivist paradigm. Collecting data through purposive techniques, namely the selection of certain informants according to research needs through interviews, participatory observations and literature studies. The results show that the right organizational policies in managing the organizational communication climate at the Support Bureau for the Promotion of Human Rights can spur employee productivity during the COVID-19 pandemic.